Adjusting for seasonal harvest bias in the lactation index for white‐tailed deer management. (18th October 2016) - Campbell, Kamen L.; Strickland, Bronson K.; Demarais, Stephen; Jones, Phillip D.; Wang, Guiming; Dacus, Chad M.; Cook, Christopher; Knox, W. Matt
ABSTRACT: Recruitment estimates are critical for making wildlife harvest decisions. White‐tailed deer ( Odocoileus virginianus ) lactation rates are often used to estimate fawn recruitment. Relatively long hunting seasons in the southern United States commonly include the period when females cease lactating, with concomitant reduction in the detection of lactation by hunters. We used 1, 587 site‐ and year‐specific lactation rates from 383 deer populations in Mississippi, Alabama, and Virginia, USA, to model the rate of decline in lactation detection across the hunting season. For each population, we calculated distance of mean female harvest date from median parturition date, and included linear, quadratic, and cubic functions of mean harvest day as potential explanatory variables. We grouped populations into 18 regions based on median conception date and tested 12 models using year and region as possible random effects. Mean female harvest occurred 92.5–210.7 days past median parturition date ( x ¯ = 148.4 days, SE = 0.5). Seasonal decline in lactation detection followed a linear trend with a daily decline of 0.25%. Given that our data contained properties where mean female harvest date varied by up to 81 days across years, this equates to a potential change in lactation index of 20% attributable only to differential detection. Adjusting hunter‐estimated lactation indices should dampen variability of annual lactation indices simply associated with harvest date of females and clarify spatial and temporal trends in recruitment needed to advise wildlife managers. © 2016 The Wildlife Society. Abstract : The accuracy of the lactation index for white‐tailed deer is subject to erosion because reproductively successful females cease lactating during the hunting season. By standardizing index values relative to peak parturition, managers can improve index accuracy and reliably compare values across hunting seasons with differing patterns of female harvest.